Pleomorphic adenoma of the hard palate: a cytology case report - BN, Swarnagowri; Sharma, Garima; Bhuyan, Madhobendra (International Journal of Advances in Medicine, 2017)
Pleomorphic adenoma is a benign tumor of the salivary glands that has elements of both epithelial and mesenchymal tissues. They represent about 60% of tumors in the parotid, are less common in the submandibular glands, and are relatively rare in the minor salivary glands. In our experience, this is the first time that we have come across Pleomorphic adenoma arising in the minor salivary glands of the hard palate.